2002
DOI: 10.1124/jpet.302.3.918
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Independent Phospholipase A2-Derived Arachidonic Acid Is Essential for Endothelium-Dependent Relaxation by Acetylcholine

Abstract: The role of calcium-independent phospholipase A 2 (iPLA 2 )-produced arachidonic acid (AA) in acetylcholine (ACh)-mediated, endothelium-dependent vascular relaxation was investigated. ACh-induced relaxation of phenylephrine-constricted isolated rat mesenteric resistance arteries was attenuated following pretreatment with (E)-6-(bromomethylene)tetrahydro-3-(1-naphthalenyl)-2H-pyran-2-one (BEL; 1 M; p Ͻ 0.01), a highly selective suicide substrate inhibitor of iPLA 2 . Following BEL, the ACh relaxation could be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
2
13
1
3
Order By: Relevance
“…Compelling evidence indicates that, in vascular smooth muscle cells, store depletion induces iPLA 2 activity. This leads to the stimulation of store-operated Ca 2ϩ -permeable channels (Wolf and Gross, 1996;Wolf et al, 1997;Seegers et al, 2002;Smani et al, 2004;Bolotina and Csutora, 2005). Because BEL, a selective inhibitor of the cytosolic ␤-isoform of iPLA 2 (Jenkins et al, 2003), totally inhibited store-operated channel activation, it has emerged as a vital tool for revealing the role of SOC channels during contractile responses in various vascular beds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compelling evidence indicates that, in vascular smooth muscle cells, store depletion induces iPLA 2 activity. This leads to the stimulation of store-operated Ca 2ϩ -permeable channels (Wolf and Gross, 1996;Wolf et al, 1997;Seegers et al, 2002;Smani et al, 2004;Bolotina and Csutora, 2005). Because BEL, a selective inhibitor of the cytosolic ␤-isoform of iPLA 2 (Jenkins et al, 2003), totally inhibited store-operated channel activation, it has emerged as a vital tool for revealing the role of SOC channels during contractile responses in various vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that phenylephrine-induced Ca 2ϩ influx is mediated solely by iPLA 2 -dependent SOC channels, because BEL pretreatment totally eliminated phenylephrine-induced contractions in mesenteric, cerebral, and carotid arteries (Park et al, 2008). Conversely, another report indicated that BEL did not affect phenylephrine contractions but inhibited acetylcholine-induced endothelium-dependent relaxation (Seegers et al, 2002). To clarify these discrepancies and establish if BEL inhibits other proteins involved in Ca 2ϩ homeostasis, we …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The pleiotropic actions of phospholipase A2 (73,84) include the stimulation of smooth muscle and endothelial cells (22,72). Altered regulation of cytosolic Ca 2ϩ activity is expected to affect a wide variety of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it recently has drawn attention as a cell growth regulator because of its possible role in insulin secretion (Ramanadham et al, 1999), eicosanoid metabolism (Akiba et al, 1998), phospholipid remodeling , apoptosis (Atsumi et al, 2000;Cummings et al, 2004), vascular relaxation (Seegers et al, 2002), and adipogenesis (Su et al, 2004). Recent studies also suggest that iPLA 2 mediates cell proliferation in HEK293 (Saavedra et al, 2006), human insulinoma, colon cancer (Bao et al, 2006;Zhang et al, 2006), and ovarian cancer cells (Song et al, 2007).…”
mentioning
confidence: 99%